Barreiras na carreira das mulheres no serviço público : uma análise do contexto da Universidade Federal do Espírito Santo - Marques, Ana Carolina Rosa (2023)
Introduction: In Brazil, as in much of the world, there has been an increase in the female presence in the productive environment over the last few decades. Although this is considered an evolution, a level of inequality persists, whereas women need to face a series of barriers to insert and develop within organizations, including in the public sphere. The enactment of the Federal Constitution of 1988 and the institution of the Regime Jurídico Único for federal public servants (Law nº 8.112/1990) enabled a more democratic scenario of access through a public tender, however, for occupying the highest positions there is no clear criteria definition, being observed in practice that the relative equality in the general quantitative does not translate into the occupation of leadership positions. In the case of the Federal University of Espírito Santo (Ufes), the problem identified is that even though they are present in a significant number within the institution, there is a predominance of women in only a few categories among the management positions held, it means, women are not distributed evenly in the different instances of university management. Therefore, the objective of this research is to analyze and describe the perception of Ufes servers (women and men) about the barriers to the development of a women career in the institution. For this, in methodological terms, the research is classified as descriptive in nature, with a quantitative approach. Data collection consisted of a survey using questionnaires in online and printed format. The data were tabulated and processed to perform descriptive statistical analyses. As a result of the dissertation, it was found that men cannot perceive the existence of barriers to the career of Ufes female servants. On the other hand, more than half of the participating women indicated the presence of gender barriers such as: receiving less recognition, less opportunity for development and difficulties in career advancement, as well as the absence of institutional policies to deal with gender discrimination. Based on the results, as a technical-technological product, an instructional material was prepared in the format of a digital booklet on gender equity in the public service, with the referral of good management practices and interpersonal relationships at work, aiming to contribute to the improvement in the academic environment and women career development within the University.